Researching the customer’s perception on EMS implementation in selected choice of hotels in Malaysia: A preliminary study on Theoretical, Methodological and Empirical Assessment - Hanafi Hamzah; Shiva Seyedeh Hashemi; Mark Kasa (International Journal Of Tourism, 2022)
Abstract: Various studies confirmed that the implementation of Environmental Management Systems in a hotel’s management and operation could lead to several effects such as cost-saving, image branding, improvement of performance, etc. Additionally, tourists’ perceptions of a destination's impacts, environmental consequences of their visits to destinations and demands for environmentally friendly products will likely play a central role in travel decision-making.Purpose: The main purpose of this preliminary study is to explore the customer perceptions on EMS implementation in selected hotels in Malaysia. This study is important to understand the customer’s behaviours towards their preferred hotels based on the understanding of environmental management systems applied in the particular hotel’s management and operations.Research methods: The study will use structured questionnaire, Descriptive Analysis, Pearson Correlation, Multiple Regression Analysis, F-test and Reliability Analysis are proposed for this study and will be performed to analyze the collected data using Statistical processing SPSS version 22.Results and discussions: The results of this study are intended to fill gaps in the literature by investigating the Malaysian present scenario on environmental management systems and adding to the body of knowledge in this area.Conclusion: The outcome of this study is expected to provide a better understanding of consumer green hotel choices in Malaysia and better account for the discrepancies between environmental believes and their actual hotel decision choices while not putting aside the quality of the service.